Nematophagous Fungi: Innovative Green Alternative Against the Worm-pests of Crops (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
Green agriculture development has an unvaluable importance for humanity in general. In terms of climate changing, globalization and the demographic progress of mankind civilization worldwide, the quality and the amounts of agricultural production are of utmost importance. Thus, the pesticide-free cultivation of crops is extremely actual for all the countries of Earth. One of the most urgent agricultural problems, costing the high expenses is the plant protection from micromycetes, bacterial and viral infections, phytophagous worms and insects, etc . Nematophagous fungi are able to trap and to consume the plant-pathogenic nematode-worms, offering the increase of yields of vegetables fruits without the pesticide application. Thus, this harmless soil hyphomycetes might have the range of applications for green technologies development as the safe alternative for pesticide-free vegetables and fruits cultivation in both greenhouses and in open ground.
Keywords: nanotechnology; priming; nanopriming; food security